Development of online learning management system on Android - Ong, Zhen Ting (2016)
With the rapid advancement of mobile technology and the global wireless internet connectivity, this has enabled people to have a convenient and instant access to information without having to depend on their notebook or personal computer. The widespread adoption of smartphones into our daily lives is increasingly common across the globe. Today, in the smartphone industry, Android garners 81% of the global smartphone market share. Thus, globally, more people are accessing the internet using Android as their primary device operating system.